Information visualization using a new focus+context technique in combination with dynamic clustering of information space - Kreuseler, Matthias; Schumann, Heidrun (NPIV'99: Proceedings of the Workshop on New Paradigms in Information Visualization and Manipulation, 1999)
This paper presents work in progress on our approach to visualizing multi-dimensional and hierarchical information. We propose two new graphical user interfaces, the Magic Eye View (MEV) and ShapeVis to explore information spaces. In order to cope with large information sets we combine MEV and ShapeVis with dynamic hierarchical clustering of information units The Magic Eye View, which implements a new Focus+Context technique, is used as the interface for visualizing those hierarchies. In order to support detailed exploration of the information space (e.g analysis of certain cluster nodes or hierarchy levels) a new technique for visualizing multidimensional information is used. ShapeVis provides 2D or 3D representations of the information objects according to the selected subset of the information space Objects are represented as small closed free-form-surfaces. The location, size and shape of these surfaces describe the original objects in the information space uniquely according to their properties.